(5x+9)/(8x-3)?

find the following for the function 

f(x+2)

f(7x)

4 Answers

Relevance
  • 1 month ago

    (5x + 9) / (8x - 3)

    f(x + 2)  = (5x + 19) / (8x - 13)

    f(7x) = (35x + 9) / (56x - 3)

    • Login to reply the answers
  • 1 month ago

    ➤ ( first part )

    f(x) = ( 5x + 9 )/( 8x - 3 )

    Numerator when when x-input is x + 2 ===> 5(x+2) + 9 = 5x + 19

    Denominator when when x-input is x + 2 ===> 8(x+2) - 3 = 8x + 13

    f(x + 2) = ( 5x + 19 )/( 8x + 13 )

    ➤ (second part )

    f(x) = ( 5x + 9 )/( 8x - 3 )

    Numerator when when x-input is 7x ===> 5(7x) + 9 = 35x + 9

    Denominator when when x-input is 7x ===> 8(7x) - 3 = 56x - 3

    f(7x) = ( 35x + 9 )/( 56x - 3 )

    • Login to reply the answers
  • Amy
    Lv 7
    1 month ago

    f(x) = (5x+9) / (8x-3)

    Hopefully you already know how to evaluate this for numbers, e.g. 

    f(7) = (5*7+9) / (8*7-3) = 44/53

    To turn f(x) into f(7) you replace all the x's with 7's.

    You can do the same with variables and more complicated expressions.

    To turn f(x) into f(y) you replace all the x's with y's.

    To turn f(x) into f(y+z) you replace all the x's with y+z:

    f(y+z) = (5(y+z)+9) / (8(y+z)-3)

    The same applies when you are asked to replace x with (x+2) or with 7x. Just be careful not to mix up the x's you are replacing and the ones that are part of the replacement.

    • Login to reply the answers
  • (5 * (x + 2) + 9) / (8 * (x + 2) - 3) =>

    (5x + 10 + 9) / (8x + 16 - 3) =>

    (5x + 19) / (8x + 13)

    (5 * (7x) + 9) / (8 * (7x) - 3) =>

    (35x + 9) / (56x - 3)

    • Login to reply the answers
Still have questions? Get your answers by asking now.